The issues of delay in construction project - Seng, Hock Sing; Saw, Hoay Ping; Tan, Poh See; Mohd Nawi, Mohd Nasrun; Osman, Wan Nadzri (2013)
The lack of completed and effective work schedule in the construction project causes conflicts at construction progress.As a result, project to be delayed.In Malaysia, the majorities attitudes of contractors are less emphasize to prepare work schedule.Thus, projects involved will over commit construction materials and human resources. From issue above, there is a need to study the techniques of work schedule for monitoring progress.With a case study provided, its findings focus on the necessity of prepare work schedule.After there has an adding work schedule, many construction phases run smoothly and construction resource also to be used wisely.